HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG KEJADIAN TANDA BAHAYA DALAM KEHAMILAN RUMAH SAKIT BHAYANGKARA MAKASSAR - andi khairul musyawir (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
ABSTRACT Objective: The objective of this study was to know the correlation between knowledge and attitude of pregnant women with the occurrence of danger sign in pregnancy at Bhayangkara Hospital Makassar. Method: Observational study with "Cross Sectional Study" approach, with a minimum sample size of 30 people with sampling technique with Simple Random Sampling. Results: The results of the study found that there was a relationship between knowledge and attitude of pregnant women about the occurrence of danger sign in pregnancy at Bhayangkara Hospital Makassar. Discussion: Causes of alarm in pregnancy vary, such as decreased appetite and continuous vomiting, pregnant women's weight does not increase, bleeding from the birth canal, swelling of the face and hands and can be followed by seizures, fetal movement diminishes even absent, fetus, or rupture of membranes prematurely. Conclusion: there can be a correlation between attitudes and attitudes of the mother hami; with the occurrence of alarm signals in pregnancy. Suggestion: Suggested health officer especially midwife always give counseling and counseling specially about danger sign in pregnancy